Analysis Of The Effect Of Company Size And Capital Structure On The Financial Performance Of The Banking Sector Listed On The Indonesia Stock Exchange In 2020-2022 - Afifah Miftakhul Jannah; Mahameru Rosy Rochmatullah (Jurnal Ekonomi, 2024)
Financial performance analysis is performed to measure the achievement of the company from the financial side. This study aims to analyze the significance of the influence of company size and capital structure on the financial performance of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. The type of data used is quantitative data with secondary data sources, namely data obtained from each banking sector company website or obtained from the official website of the Indonesia Stock Exchange (IDX) www.idx.co.id. the sample used in this study were 29 companies. Sampling technique using purposive sampling method. The method of data collection using documentation with data analysis techniques using classical assumption test, multiple regression analysis, coefficient of determination, t test, and F test. The results of this study indicate that the size of the company has a significant positive effect on the company's financial performance. While the capital structure has a significant negative effect on the company's financial performance.